Is it necessary to walk the talk? The effects of maternal experiences and communication on the sexual behavior of female adolescents - Susan L. Averett; Sarah M. Estelle (Institute for the Study of Labor (IZA), 2012)
Numerous social marketing campaigns exhort parents to talk to their children about sexual abstinence and pregnancy/STD prevention while child-development experts advise parents to initiate discussions about reproductive health and related values at an early age. The efficacy of these marketing campaigns and the precise impact of ongoing dialogue between parents and children are difficult to ascertain, however, if parents are more likely to broach related topics with adolescents with otherwise greater propensities for risky behavior. While extant research recognizes the importance of family environment and parenting activities, little has been done to separately control for the various aspects of parenting that might confound the influence of the marketing campaigns. We separately identify the effects of parenting style, a parent's own risky behavior, and the parent's communication about sex on her adolescent's sexual behavior. OLS models indicate that female adolescents with less strict parents, whose mothers gave birth as teenagers, or whose mothers communicate more about sex are more likely to have sexual intercourse, practice unsafe sex, and engage in casual sex. After controlling for the endogeneity of parental talk, though, we find that an increase in parental talk neither increases nor decreases the probability an adolescent has had sex, unsafe sex, or casual sex. The only exception is a strongly significant result that more communication about sex from mothers who were themselves teen mothers actually increases the probability a daughter has had sex.
urn:nbn:de:101:1-201303202211
Keywords: I13; J12; 330; parental sex talk; sexual intercourse; unsafe sex; casual sex; teen mother; Sexualität; Kommunikation; Mütter; Jugendliche; Schwangerschaft; USA